Malate Exudation by Six Aerobic Rice Genotypes Varying in Zinc Uptake Efficiency - Gao, Xiaopeng; Zhang, Fusuo; Hoffland, Ellis (Journal of environmental quality, 2009)
Zinc (Zn) uptake by plant roots from soils low in plant-available Zn may be increased by Zn-mobilizing rhizosphere processes, including exudation of low-molecular-weight organic anions. A rhizotron experiment with a low Zn clay soil and a nutrient solution experiment were conducted to test if this occurs in six rice (Oryza sativa L.) genotypes varying in tolerance to low Zn supply. In both experiments, low Zn supply resulted in a marked decrease in biomass production of most genotypes compared with adequate Zn supply. The genotypes showed a significant variation in Zn efficiency. Plants responded to low Zn supply with increased root exudation of malate in both experiments. The malate concentration in the rhizosphere of three genotypes ranged from 0.22 to 0.59 mmol L–1 in rhizotron experiment, and the malate exudation rate of five genotypes ranged from 0.18 to 0.53 nmol g–1 root dw s–1 in the nutrient solution experiment. On average, low Zn supply in the rhizotron experiment increased rhizosphere malate concentration by 64% compared with that at adequate Zn supply. The averaged malate exudation rate at low Zn in the nutrient solution experiment was 40% greater than at adequate Zn supply. The malate exudation of rice genotypes at low Zn was not correlated to Zn efficiency or Zn uptake in either experiment. Based on a soil malate extraction experiment, the observed genotypic difference in rhizosphere malate concentration is expected to have a negligible effect on the concentration of Zn in soil solution. These findings suggest that Zn mobilization by rice genotypes cannot be explained by increased malate exudation alone, indicating that other mechanisms contribute to the variation in plant Zn uptake. The results also emphasize that effects of root exudates on soil properties need to be assessed to evaluate the role of root exudation in nutrient mobilization.